The Trans-Pacific Partnership : a Quest for a Twenty-first Century Agreement. - Lim, C. L. (Cambridge University Press, 2012)
An examination of the Trans-Pacific Partnership (TPP)? a trade agreement that aspires to set the benchmarks for future deals.